2005
DOI: 10.1075/intp.7.1.04ahr
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic phenomena in simultaneous interpreting

Abstract: This paper reports on an empirical study on prosody in English-German simultaneous interpreting. It discusses prosody with particular reference to its tonal, durational and dynamic features, such as intonation, pauses, rhythm and accent, as well as its main functions, i.e. structure and prominence. Following a review of previous studies on the topic, a conceptual approach for the analysis of prosody in terms of structure and prominence is developed and subsequently applied to an authentic corpus of professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 0 publications
3
17
0
2
Order By: Relevance
“…Tissi (2000) found that the occurrence of silent pauses in interpreters' delivery is related to those in the ST. In her experiment, both the ST and TTs have a high incidence of pauses between 0.25 and 1.25 seconds but the TTs also have a remarkable incidence of pauses between 2.5 and over 5 seconds that do not exist in the ST. Ahrens (2005), in the analysis of prosodic patterns in a corpus of authentic professional simultaneous interpretations from English to German, found that prosodic features in the target texts show 'certain characteristics that are specific to simultaneous interpreting' (p. 51) and that there are fewer but proportionally longer pauses in TTs than in the ST.…”
Section: Characteristics Of Pauses In Interpretingmentioning
confidence: 97%
“…Tissi (2000) found that the occurrence of silent pauses in interpreters' delivery is related to those in the ST. In her experiment, both the ST and TTs have a high incidence of pauses between 0.25 and 1.25 seconds but the TTs also have a remarkable incidence of pauses between 2.5 and over 5 seconds that do not exist in the ST. Ahrens (2005), in the analysis of prosodic patterns in a corpus of authentic professional simultaneous interpretations from English to German, found that prosodic features in the target texts show 'certain characteristics that are specific to simultaneous interpreting' (p. 51) and that there are fewer but proportionally longer pauses in TTs than in the ST.…”
Section: Characteristics Of Pauses In Interpretingmentioning
confidence: 97%
“…For purposes of comparison between written and oral output, we have defined a pause in both written and sight translation as an interruption in the writing or speech process of 2 seconds or more. When analyzing oral output, a distinction is often made between filled and unfilled pauses (Ahrens 2005;Mead 2000), where filled pauses typically consist of hesitation markers, while unfilled pauses are defined as silence intervals. In the present analysis we will focus on unfilled pauses.…”
Section: Pause Analysismentioning
confidence: 99%
“…Both Shlesinger (1994) and Ahrens (2005) emphasize the importance of SI-specific factors in determining salient features of intonation in the output of simultaneous interpreters. Shlesinger (1994) examines the role of intonation in the production and perception of simultaneously interpreted texts: one salient feature she reports in the TL output of interpreters is incompatibility of syllabic stress with semantic contrast (Shlesinger 1994: 231).…”
Section: Introductionmentioning
confidence: 97%
“…This means that: (1) the perception of SL suprasegmentals occurs at the same time as the production of TL suprasegmentals; (2) the interpreter's output as a whole is based on incomplete SL input, as opposed to the complete turns on which consecutive interpreting is based. These characteristics of the SI process can understandably have a distinctive effect on salient suprasegmental features of the interpreter's TL output such as pausing patterns, which might differ from those of spontaneous monolingual speech (Barik 1972(Barik , 1973Goldman-Eisler 1972;Lee 1999), intonation and stress (Ahrens 2005;Nafá Waasaf 2007;Shlesinger 1994;Williams 1995).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation